Home » If y = (frac{x}{x – 3}) + (frac{x}{x + 4}) find y when x =…

If y = (frac{x}{x – 3}) + (frac{x}{x + 4}) find y when x =…

If y = (frac{x}{x – 3}) + (frac{x}{x + 4}) find y when x = -2

  • A.
    -(frac{3}{5})
  • B.
    (frac{3}{5})
  • C.
    -(frac{7}{5})
  • D.
    (frac{2}{5})
Correct Answer: Option A
Explanation

y = (frac{x}{x – 3}) + (frac{x}{x + 4}) when x = -2
y = (frac{-2}{-5}) + (frac{(-2)}{-2 + 4})
= (frac{2}{5}) + (frac{-2}{2})
= (frac{4 -10}{10})
= (frac{-6}{10})
= -(frac{3}{5})